REKONSTRUKSI PENAMPANG STRUKTUR SEIMBANG (BALANCED CROSS-SECTION) PADA AREA REMBESAN GAS DI FORMASI RAMBATAN, KALI PEKACANGAN, KECAMATAN BANJARMANGU, KABUPATEN BANJARNEGARA - , MOCHAMAD AZIS QOSIM NUR SECHA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The North Serayu Basin is one of two basins in Central Java. In this basin, a number of hydrocarbon seepages have been reported, suggesting a petroleum system exists (Satyana, 2007). However, tectonic intricacy makes this area a relative âterra-incognitaâ in terms of Java exploration. As a surface manifestation, hydrocarbon seepage is a window to study subsurface geological conditions and the petroleum system. Therefore, this research focused on the geological factors that cause the hydrocarbon seepages at Sijenggung, Banjarmangu District, Banjarnegara Regency, Central Java. In the study area, gas seepage was found in the Rambatan Formation. The methods used in this study consist of surface geological data collecting, including geological structures and measured stratigraphic data. The study area is located in Pekacangan River. Tectonic events constructing the study area started with the subsidence of the North Serayu Basin as a back-arc basin in the Middle Miocene, changed into a volcanic arc in the Late Miocene, and then returned to back-arc setting, and experienced massive foldings in the Pliocene. Finally, reactivation of volcanism occurred in the Pleistocene. These tectonic events affected the deposition of the Rambatan Formation that consists of shale, marl, and tuff. From nannofossil analysis, it is known that this formation was deposited until Early Pliocene. The massive initial thickness (due to the long term of deposition) was then multiplied by extreme recumbent folding as the result of the north-south compression created by Pleistocene volcanic loading. The large initial thickness added to by the recumbent folding drove the Rambatan Formation to maturity and reached the gas window in the Pleistocene. Thrust faults divided the whole recumbent fold into smaller compartments, also allowed the hydrocarbon to dissipate directly from the source rock to the surface